2023
DOI: 10.1186/s12967-023-03930-0
|View full text |Cite
|
Sign up to set email alerts
|

FYN: emerging biological roles and potential therapeutic targets in cancer

Abstract: Src family protein kinases (SFKs) play a key role in cell adhesion, invasion, proliferation, survival, apoptosis, and angiogenesis during tumor development. In humans, SFKs consists of eight family members with similar structure and function. There is a high level of overexpression or hyperactivity of SFKs in tumor, and they play an important role in multiple signaling pathways involved in tumorigenesis. FYN is a member of the SFKs that regulate normal cellular processes. Additionally, FYN is highly expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 185 publications
1
10
0
Order By: Relevance
“…Fyn regulates multiple signals by phosphorylating signaling molecules and thus participates in physiological processes. [ 28 , 29 ] From the published papers, the effects of Fyn on kidney disease are consistent with our study. For example, activated Fyn augments oxidative stress, inflammation, endoplasmic reticulum stress, and autophagy dysfunction, resulting in the progression of acute kidney disease (AKI).…”
Section: Discussionsupporting
confidence: 91%
“…Fyn regulates multiple signals by phosphorylating signaling molecules and thus participates in physiological processes. [ 28 , 29 ] From the published papers, the effects of Fyn on kidney disease are consistent with our study. For example, activated Fyn augments oxidative stress, inflammation, endoplasmic reticulum stress, and autophagy dysfunction, resulting in the progression of acute kidney disease (AKI).…”
Section: Discussionsupporting
confidence: 91%
“…FYN plays an essential role in diverse cellular processes 28,29 . In addition, previous studies showed that FYN served as a tumor accelerator in multiple cancers 17,30,31 . Moreover, Liu et al disclosed that FYN expression was elevated in EC tissue specimens, and FYN silence restrained cell growth and facilitated apoptosis in EC cells 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 29 In addition, previous studies showed that FYN served as a tumor accelerator in multiple cancers. 17 , 30 , 31 Moreover, Liu et al disclosed that FYN expression was elevated in EC tissue specimens, and FYN silence restrained cell growth and facilitated apoptosis in EC cells. 19 , 20 Here, FYN was also observed to be overexpressed in EC tissue specimens and EC cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTPs are known to be signaling molecules that regulate a variety of cellular processes [ 46 ]. FYN (FYN proto-oncogene, Src-family tyrosine kinase) is a member of the protein–tyrosine kinase oncogene family that plays roles in many biological processes, including regulating cell growth and survival, cell adhesion, integrin-mediated signaling, cytoskeletal remodeling, cell motility and the immune response [ 47 ]. As well as the strong signals from the immune-system processes, some other interesting pathways were highlighted in the commercial birds.…”
Section: Discussionmentioning
confidence: 99%